2020
DOI: 10.1212/nxi.0000000000000739
|View full text |Cite
|
Sign up to set email alerts
|

Brain amyloid in virally suppressed HIV-associated neurocognitive disorder

Abstract: ObjectiveTo determine whether virally suppressed HIV neuropathogenesis, a chronic neuroinflammatory state, promotes abnormal brain amyloid deposition.MethodsA total of 10 men with virally suppressed HIV-associated neurocognitive disorder (HAND), aged 46–68 years, underwent 11C-labeled Pittsburgh compound B PET. Data from the Australian Imaging, Biomarkers and Lifestyle (AIBL), including 39 cognitively normal individuals (aged 60–74 years), 7 individuals with mild cognitive impairment (MCI) (aged 64–71 years), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 47 publications
(76 reference statements)
1
22
0
Order By: Relevance
“…While Alzheimer’s disease is characterized by neuritic, extracellular amyloid plaques, studies of HAND tissue show diffuse and intracellular expression of amyloid-β that may be a precursor to neuritic plaques [ 46 , 50 , 51 ]. However, more recent PET imaging studies measured amyloid deposition in the brains of living HAND patients and did not show amyloid-β accumulation [ 52 55 ], and a recent neuroimaging study reported no change in amyloid levels in virally suppressed patients [ 56 ]. The conflicting results from these studies may be due to different factors.…”
Section: Neuroimaging and Neuropathological Studies In Hand Patientsmentioning
confidence: 99%
“…While Alzheimer’s disease is characterized by neuritic, extracellular amyloid plaques, studies of HAND tissue show diffuse and intracellular expression of amyloid-β that may be a precursor to neuritic plaques [ 46 , 50 , 51 ]. However, more recent PET imaging studies measured amyloid deposition in the brains of living HAND patients and did not show amyloid-β accumulation [ 52 55 ], and a recent neuroimaging study reported no change in amyloid levels in virally suppressed patients [ 56 ]. The conflicting results from these studies may be due to different factors.…”
Section: Neuroimaging and Neuropathological Studies In Hand Patientsmentioning
confidence: 99%
“…High Cu 2+ that outcompetes Zn 2+ for correct folding, activity, or multimerization of essential cellular proteins as BMCs may rather nucleate their aggregation as insoluble pathological plaques of neurodegenerative diseases (Figure 2A). Indeed, virus infections have been shown to exacerbate neurodegenerative disease phenotypes [68][69][70][71][72], and just as Zn 2+ supplementation has been successfully used as treatment against many viruses [160], Zn 2+ supplementation is also described as a paradigm-shifting practice for neurodegenerative disease associated with Zn 2+ and/or Cu 2+ homeostasis abnormalities [316]. Elevated Cu/Zn ratios central to so many diseases, combined with the essential role of Zn 2+ for BMC formation regulating many cellular processes, suggests that prolonged altered Cu/Zn ratios may represent an underappreciated and underlying feature of diseases (Figure 2).…”
Section: Figurementioning
confidence: 99%
“…Our findings are supported by reports that modulation in Cu/Zn ratios and altered expression of proteins maintaining cellular and physiological ion homeostasis are hallmarks of both virus infections and neurological diseases. We and others have contributed to the greater body of literature promoting the theory that towards their own replicative benefit, underlying virus infections induce neurocognitive disorders and may exacerbate neurological diseases [ 68 , 69 , 70 , 71 , 72 ]. We extend this concept, demonstrating that viruses alter metal ion homeostasis and Cu/Zn ratios, creating cell-clogging, insoluble pathological prion-like aggregates of proteins otherwise undergoing LLPS supporting normal cellular functions.…”
Section: Introductionmentioning
confidence: 99%
“…42,43 However, recent PET studies do not show major differences in amyloid deposition stratified by HIV serostatus or HAND severity. 44,45 Others propose that cognitive impairment in PLWH in the ART era might be related to cerebrovascular diseases. 46 Asymptomatic intracranial atherosclerosis has been increasingly recognized as a risk factor of cognitive impairment in the general population.…”
Section: Application Of Nuclear Imaging To Understand Neurohivmentioning
confidence: 99%